Warehouse management model to reduce return rate applying lean manufacturing techniques and multicriteria ABC in a SMES in the textile sector - Roncal Coronel, Milagros Liliana (2024)
The textile industry represents 6.4% of the G.D.P., which has a high demand for orders with fast and correct deliveries. Nevertheless, there is a rate of returns that has been increasing in the last few years due to the high number of orders received. For this reason, the article is based on a case study of a SME.That sells children's clothing in Peru. A model was developed using 5s methodology, ABC Multicriteria, Jidoka, and Standardized Work, seeking to improve the current 7.14% of returns. The proposed model was implemented with a pilot plan and simulated with Arena Software, proving that the combination of Lean methodologies can optimize the warehouse processes, reducing the rate of returns to 4%.